A “Green” Primary Explosive: Design, Synthesis, and Testing - Tang, Jie; Chen, Dan; Zhang, Gen; Yang, Hongwei; Cheng, Guangbin (Synlett, 2019)
This account presents the synthesis and the characterization of triazine-tetrazine nitrogen heterocyclic compounds. Some compounds were characterized by NMR and IR spectroscopy, mass spectrometry, differential scanning calorimetry (DSC), and single-crystal X-ray diffraction. The physical and chemical properties were obtained by EXPLO5 v6.01, gas pycnometer, BAM Fallhammer, BAM Friction tester, and several detonation tests. The results show that the new metal-free polyazido compound 3,6-bis-[2-(4,6-diazido-1,3,5-triazin-2-yl)-diazenyl]-1,2,4,5-tetrazine (4) with high heat of formation (2820 kJ mol–1/6130.2 kJ kg–1) and excellent detonation velocity and pressure (D = 8602 m s–1, P = 29.4 GPa) could be used as ingredient in secondary explosives. 3,6-Bis-[2-(4,6-diazido-1,3,5-triazin-2-yl)-hydrazinyl]-1,2,4,5-tetrazine (3) can detonate research department explosive (RDX, cyclonite) as a primer (ΔfHm = 2114 kJ mol–1/4555.2 kJ kg–1, D = 8365 m s–1, P = 26.8 GPa), whose initiation capacity is comparable to that of the traditional primary explosive Pb(N3)2. Therefore, the metal-free compound 3 can potentially replace lead-based-primary explosives, which would be advantageous for the environment.1 Introduction2 Strategies to Form High-Nitrogen Compounds with High Heat of Formation3 Metal-Free Strategies to Prepare Primary Explosives4 Concluding Remarks
Keywords: high-nitrogen energetic compounds; tetrazines; nucleophilic substitution; metal-free primary explosive